Al – Jahiz’s Rational Epistemology : An Analysis of His Scientific Contribution to the Intellectual Dynamics of the Abbasid Dynasti - Arif Rahman Harefa; Kacar Ginting; Rijalul Faizul Ichsan; Ira Annisa; Tien Suhaila (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
Islamic civilization during the abbasid era market the pinnacle of intellectual achievement, characterized by rapid advancements in science through the integration of Greek, Persian, and Indian traditions. In this context, Al-Jahiz emerged as a multidisciplinary thinker who combined rational and empirical approaches in his study aims to analyze the dynamics of knowledge development during the Abbasid era, to examine Al-Jahiz’s contributions, and to explore his rational epistemology. The research employs a qualitative approach based on library research using historical and philosophical methods, with the primary source being Kitab Al-Hayawan, analyzed through content analysis. The Abbasid era was supported by a conducive intellectual ecosystem, such as political support, freedom of thought, and openness to various scientific traditions.